MODALITAS SPECULATIVE DARŌ DAN PADANANNYA DALAM BAHASA INDONESIA - Chan Rizkia Anggia Vici; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Speculative darō is a sub category of epistemic modality which discusses about belief or disbelief in the speaker’s attitude towards a certain proposition that is frequently translated as mungkin in Indonesian. This research explains about the function and the meaning of speculative darō and its equivalent in Indonesian based on the theory of Heiko Narrog (2009) and Hasan Alwi (1992). The methods used is distributional method. The result, speculative darō is used to convey the conclusion and belief of the speaker, to express the speaker’s hyphothesis of the subject’s action and situation, to express a yet to be concluded subjective possibility and speculation. The meaning of speculative darō is there in ‘kepastian’ with the prepositional form (saya merasa yakin and saya merasa pasti), and adverb (pasti, tentunya and tentu); ‘keteramalan’ with the prepositional form (menurut pendapat saya and menurut hemat saya), adverb (kelihatannya), main verb (saya pikir); ‘kemungkinan’ with adverb (mungkin, dapat saja, bisa saja, bisa jadi, boleh jadi).Key Words: Speculative Darō, Function and Meaning, Equivalent